Statistical comparison of soil analysing results of chernozem soils - Víg, Róbert; Dobos, Attila; Pongrácz, Zoltán (Acta Agraria Debreceniensis, 2008)
The soil fertility was degraded as a result of unreasonable tillage, therefore the application of site-specific nutrient replacement is necessary. It is essential for the application of precision fertilization to know the location, extension, soil properties and nutrient-supply of the different soil types ofcultivated areas.We collected soil samples from 580 hectares of land in 2006. Soil samples were collected from every 5 ha in 30 and 60 cm depths during Spring from 20.05.2006 to 12.06.2006 and again in Autumn from 09.19.2006 to 02.10.2006. Soil samples were analysed at the Department of Agricultural Chemistry and Soil Science of DE-ATC.The two examined soils are slightly calcareous, weakly saline, poor in zinc. The calcareous chernozem soil is slightly acid, the content of humus, nitrogen, phosphorus and potassium is medium in this soil. The meadow chernozem soil is slightly alkaline, and properly supplied with humus and potassium, and middling supplied with nitrogen and phosphorus. The meadow chernozem soil is more heterogenous in soil plasticity, lime, saline, nitrogen phosphorus and potassium content and less heterogenous in pH and zinc content than the calcareous chernozem soil.Standard deviation of measured values in pH, soil plasticity, humus and nitrogen content significantly differ between the examined soil types. The soil plasticity, pH, humus, nitrogen and zinc content significantly differ among calcareous chernozem soil and meadow chernozem soil, but the difference in phosphorus content can be statistically proven only in case of Spring soil sampling.